DAMPAK PROGRAM CORPORATE SOCIAL RESPONSIBILITY(CSR) HINTERLAND SUPPORT PT.MCDERMOTT INDONESIA DI KECAMATAN GALANG 2017-2018 - Amirah, Dwi Resti; ", Afrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This research aims to analyze the effectiveness of PT.McDermott Indonesia's Corporate Social Responsibility (CSR) program that is Hinterland Support on the Community in Batam. The purpose of this research are to find out and to describe the impact of the Hinterland Support throughout its programs to Community in Galang. The Hinterland area of Batam has not fully had access to adequate facilities. PT.McDermott Indonesia is committed and brings their awareness about those issues and fix it by their own CSR program.This research is a qualitative research, which is done by explaining the case based on facts. Neo liberalism theory helps to analyze the role of non nation actor, which is Multinational Corporation. Another theoretical framework applied in this research are Corporate Social Responsibility theory and also group analysis to assisting the researcher to find the answers in this case. The techniques used to collect data to study the case of library research in the form of journals, books, an official document, articles, and websites.The result of this research shows that the Hinterland Support program in the form of renovation and development  has given impacts on the people of Batam City since it was established in 2002. Even though it is not implemented every year, in the first ten years of its operation, Hinterland Support focuses on building public facilities that help the Hinterland area community. The program brought impacts and achieved the main goal of the program that are make the community sourced and sustainability.  Keyword(s) : CSR, Impact, MNC, Hinterland Support, Galang, Batam